Spherical tokamaks with a high current carrying plasma center column - Lampugnani, Leandro Gabriel (2018)
Spherical tokamaks (STs) have many advantages from the perspective of a fusion reactor. A further improvement would be to replace the center post by a plasma center column (PCC). In this case, biased electrodes could be used to drive current along the PCC and produce the toroidal magnetic field. Moreover, the magnetic helicity injected (HI) by the PCC can be used to form and sustain the configuration, via magnetic relaxation. The magnetic structure and stability of these so-called ST-PCC configurations are studied in detail. In particular, it is shown that stable equilibria with tokamak-like safety factor (q) profiles can be obtained in the regime of high PCC current and moderate poloidal flux amplification. Using numerical simulations, the feasibility of forming and sustaining ST-PCC configurations via HI is demonstrated. The sustainment in this case involves a significant level of fluctuations and is shown to occur at a marginally stable configuration having a q = 1 surface in the ST. This behavior is in close analogy to that of spheromaks sustained by a coaxial plasma gun but presents two major differences. First, the current density in the open flux region (PCC) is significantly larger. Second, the mean current density gradient in the ST has the opposite sign, leading to q profiles with regular magnetic shear (i.e., q increases from the magnetic axis to the separatrix, as in tokamaks). When helicity injection is switched off, the fluctuations decay and nested, closed magnetic surfaces appear. This opens the possibility of using HI to form the ST-PCC and a combination of auxiliary current drive (neutral beams and/or RF) and high bootstrap current to sustain a fluctuation free configuration.